Digital Imaginaries of the Pandemic-Resilient City. - Crampton, Jeremy (RWTH Aachen University, 2021)
Planning is a form of imagination, and the COVID-19 pandemic has both solidified and loosened it. Pandemic responses such as locational track and trace, facial recognition tracking, and machine-learning renew forms of top-down surveillance. Yet the pandemic also witnessed new forms of thinking: the digital right to the city, reclaiming public space and roads from cars, low-traffic neighbourhoods, slow streets, green spaces, and better cycle lanes. In this contribution, I explore how digital geolocational technologies can build the pandemic-resilient city. Drawing on an alternative imaginary grounded in slow AI I assert that it is time to think big by learning from the COVID-19 pandemic to build safe, equitable activity spaces and geographies. I assess how innovative digital spatial technologies and human-in-the-loop geographic machine learning can capture, map, and analyse positive changes, and how geographic technologies can help build a radically resilient city.
Keywords: Stadtforschung; Digitalisierung; Informationstechnologie; Kommunikationstechnologie; Öffentlicher Raum; Resilienz; Stadtplanung; Corona-Krise